Properties of Natural Polymer Modified Mortar - Goyal, Ankur (My University, 2016)
Green construction material plays an important role in sustainable development. Brundtland Report (1987) about sustainability has driven the global concept of sustainable development as well as the sustainability of infrastructure. Since concrete has become the most popular construction material in the world, sustainable concrete will determine the sustainability of infrastructure. Several efforts have been done to achieve the sustainable concrete. Methods to achieve the objectives can be (for example) the use of less energy in making concrete, reduction of CO2 emission by using natural additives, reduction in use of natural aggregates via replacement by recycled aggregates. One of the modern concepts to make concrete a green construction material is, “Triangle of Virtuous Concrete Principle”. The “Triangle of Virtuous Concrete Principle” requires the three parameters of sustainable development, infrastructure development and carbon footprint reduction simultaneously. Connecting the three aspects in the “Triangle of Virtuous Concrete Principle”, concrete will truly become virtuous and green construction material. Sustainable concrete needs ‘extra’ life-time that means longer durability. Hence, concrete shall be stronger, denser, and more durable. For the last few decades, polymer cementitious materials have been added to concrete to improve its performance and to enhance its properties. For application, polymer added into mortar or concrete which is called polymer mortar or polymer concrete. When polymer added together with cement and also aggregate into mortar or concrete, it is called polymer modified mortar or polymer modified concrete. Polymer modified cementitious material exhibits improved binding properties and adhesion to aggregates; therefore it is useful for concrete repairing and retrofitting in modern construction. In Polymer Modified Mortars (PMM) aggregates are bound by a matrix phase resulting in superior properties compared to the conventional mortar. Since most of the polymers are derived from petroleum, which is a non-renewable resource it will end someday. Today’s energy matrix is mainly based on fossil fuels like petroleum oil, coal and natural gas, which covers more than 80% of total worldwide energy consumption. Alternatives to petroleum-based products are one of the main interests of researchers. Natural oils occur in nature, can be extracted and are renewable. Natural oils such as soybean, corn, linseed, castor and seaweeds, when synthesized produce natural polymers. They are renewable, iv offer comparable performance and of low cost when compared with petroleum-based polymer matrices. These materials have also environmental advantages over petroleum-based materials. In this study, polymer modified mortar is designed by using natural polymer from seaweeds. The research is conducted in two phases, pilot study and main-experiment. Pilot Study aimed to investigate the compressive strength of natural mortar modified with seaweed gel (Eucheuma Cottonii) and seaweed powder (Eucheuma Cottonii). From the preexperiment results it was observed that mortar modified with seaweed powder gave better compressive strength. Therefore, seaweed powder was selected for main experiment. The main experiment was conducted by modifying mortar with seaweed powder as an additive in varying compositions of 0.5%, 1%, 1.5% and 2% of cement by weight. Compressive strength was evaluated for this mortar at 7 days and 28 days of curing. Split tensile strength was also evaluated at 28 days curing. Durability properties were also tested for water sorptivity and Rapid Chloride Permeability Test (RCPT). Slant Shear test was also performed to check the bond strength of 28 day cured conventional mix repaired with fresh Polymer Modified Mortar and then cured for 7 days. XRD analysis was also performed on the samples to check the products formed during the hydration reaction. The results from this analysis are used to interpret the results of mechanical and durability tests. The research has shown that natural polymer modified mortar with mix composition of seaweed powder of 1% of cement by weight exhibited the maximum enhancement in the compressive strength and split tensile strength and significant improvement in the durability properties and bond strength.
Master of Engineering-Structures
Keywords: Seaweed; Natural Polymers